2019
DOI: 10.1055/a-0897-8785
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Related Quality of Life in Elderly with Subclinical Hypothyroidism and Improvement on Levothyroxine is Distinct from that in Young Patients (TSAGE)

Abstract: The aim of this study was to investigate in a longitudinal approach whether levothyroxine (LT4) substitution has a different impact on quality of life (QoL) and thyroid related QoL in younger (<40 years) and older subjects (>60 years) with elevated thyroid-stimulating hormone (TSH) concentrations. The study included male and female patients with newly diagnosed, untreated subclinical hypothyroidism defined by TSH>8 mU/l. Patients were recruited throughout Germany from 2013–2016 and evaluated by clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…However, this is not the end to all age considerations, since a recent small longitudinal study of patients with newly diagnosed and untreated hypothyroidism in Germany (TSAGE) revealed a significant benefit in quality of life in T 4 treated elderly individuals with TSH concentrations above 8 mU/L. Furthermore and importantly the study also underlined that quality of life parameters linked to thyroid function and dysfunction are different in young and old patients [32]. Together these findings illustrate that much further research is required to get more pieces of the puzzle together in order to ultimately define who and how young and old, female and male patients may benefit best from treatment of thyroid dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…However, this is not the end to all age considerations, since a recent small longitudinal study of patients with newly diagnosed and untreated hypothyroidism in Germany (TSAGE) revealed a significant benefit in quality of life in T 4 treated elderly individuals with TSH concentrations above 8 mU/L. Furthermore and importantly the study also underlined that quality of life parameters linked to thyroid function and dysfunction are different in young and old patients [32]. Together these findings illustrate that much further research is required to get more pieces of the puzzle together in order to ultimately define who and how young and old, female and male patients may benefit best from treatment of thyroid dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…Observational data in subjects with subclinical hypothyroidism (diagnosed using a cut-off for thyrotropin of 8 mIU/L) showed that a similar overall improvement from baseline in health-related quality of life occurred following LT4 treatment in younger (<40 years) and older (>60 years) patients [34]. Both age groups benefitted from improvements in "Emotional Susceptibility" and "Impaired Daily Life" domains; older patients additionally improved their score for "Tiredness" and younger patients improved their score for "Cognitive Complaints".…”
Section: Observational Studies Of Levothyroxine In Older Patients Witmentioning
confidence: 93%
“…In Sawicka-Gutaj et al's (2018) open-label study of QoL and an impaired sex life in patients with autoimmune hypothyroidism, the impairment was worse in older patients [84]. Djurovic et al's (2018) study of LT4-treated patients with Hashimoto thyroiditis found that QoL was more impaired in patients aged over 50 [86], and Recker et al (2019) observed partial and inconsistent impairments in ThyPRO and SF-36 in both older patients (aged 60-75) and younger patients (under 40) with SCH before and after treatment [89]. However, a post-hoc analysis of Djurovic et al's data suggested that poor QoL was related to weight gain [73].…”
Section: Other Factorsmentioning
confidence: 99%
“…The results of nonrandomized studies [either cross-sectional or longitudinal (Table 3)] were disparate: some studies found no significant differences in QoL between treated patients and healthy controls [69,101], others observed better scores in some but not all QoL domains in treated patients [13,68,84,89], and yet others reported the presence or persistence of significantly worse QoL in treated patients [23,58,66,73,86].…”
Section: Nonrandomized Studiesmentioning
confidence: 99%